2006
DOI: 10.1111/j.1600-0633.2006.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Major difference in mercury concentrations of the African big barb, Barbus intermedius (R.) due to shifts in trophic position

Abstract: The African big barb (Barbus intermedius, R.) from Lake Awassa, Ethiopia is an important fish species, especially with the ongoing decline of the Nile tilapia (Oreochromis niloticus, L.) fishery. Their diet and habitat use was studied using stomach content analyses, stable nitrogen and carbon isotopes, and transect netting. Mercury biomagnification was also determined. The big barb was found to primarily exist in the littoral habitat, with molluscs being their predominant food item. The proportion of small fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
25
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 59 publications
7
25
1
Order By: Relevance
“…For example, piscivorous big Barbs (Labeobarbus intermedius) in Lake Hawassa has exceeded the marketing limit of the European Union 0.5 mg/kg [7]. It has been reported that Hg concentrations are significantly higher in L. intermedius than in Clarias gariepinus and Oreochromis niloticus in Lake Hawassa [9] and Koka [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, piscivorous big Barbs (Labeobarbus intermedius) in Lake Hawassa has exceeded the marketing limit of the European Union 0.5 mg/kg [7]. It has been reported that Hg concentrations are significantly higher in L. intermedius than in Clarias gariepinus and Oreochromis niloticus in Lake Hawassa [9] and Koka [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is present in Ethiopian rift valley basin, Abay basin and Baro-Akobo basin part of Ethiopia, where Lake Tana harbor the largest population (Vijverberg et al, 2012;Awoke, 2015). It is one of the most commercially important fish species in the country (Desta et al, 2006;Bjørklis, 2004). The total annual yield of L. intermedius from the total inland water bodies is estimated to be about 365 tonnes per year (LFDP, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License overfishing and parasitic infection has resulted in less accessibility of the fish in the local markets (Desta et al, 2006;Mengesha, 2009;Dadebo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely distributed in the rift valley basin, Abay basin and Baro-Akobo basin part of Ethiopia, of which Lake Tana harbors the largest number of big barb species (Vijverberg et al, 2012;Awoke, 2015). It is one of the most commercially important fish species in the country (LFDP4, 1997;Bjørklis, 2004;Desta et al, 2006). The total annual yield of L. intermedius from the total inland water bodies is estimated to be about 365 tons per year (LFDP, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, recently L. intermedius catch from rift valley lakes (Lake Hawassa and Lake Koka) declined and reported to be unsafe for human consumption due to high mercury concentration (Mengesha, 2009). The decline of the fish species due to overfishing and parasitic infection has result the less accessibility of the fish on the local markets (Desta et al, 2006;Mengesha, 2009;Dadebo et al, 2013). Length-weight relationship (LWR) is one of the most important biological tools in fishery management.…”
Section: Introductionmentioning
confidence: 99%